Cooperation in international banking supervision - Cornelia Holthausen; Thomas Rønde (European Central Bank (ECB), 2004)
This paper analyzes cooperation between sovereign national authorities in the supervision and regulation of a multinational bank. We take a political economy approach to regulation and assume that supervisors maximize the welfare of their own country. The communication between the supervisors is modeled as a 'cheap talk' game. We show that: (1) unless the interests of the countries are perfectly aligned, Þrst best closure regulation cannot be implemented; (2) the more aligned the interests are, the higher is welfare; (3) the bank can allocate its investments strategically across countries to escape closure.
Keywords: F36; G21; G28; L51; 330; cheap talk; closure; multinational banks; supervision